Does immediate orthostatic hypotension in adults have clinical implications for syncope and falls? An analysis of the Irish longitudinal study of ageing. - Reddin, Catriona; Briggs, Robert; Knight, Silvin P; Kenny, Rose-Anne (Age & Ageing, 2026)
Background and Aims Orthostatic hypotension is a common cause of syncope and falls; however, it is unclear if the association differs by variant. One of the variants is immediate orthostatic hypotension (formerly initial), which may be of lesser clinical importance than other variants. The Irish Longitudinal Study of Ageing offers a unique opportunity to evaluate the association of orthostatic hypotension variants with falls and syncope events in adults 50 years and older. Methods Blood pressure (BP) and heart rate were measured supine and standing using phasic blood pressure techniques. Initial OH was defined as a drop in systolic BP >40mmHg and/or diastolic BP >20 mm Hg at 10 seconds after standing, with recovery to within 20mmHg of baseline Systolic BP and 10 mmHg diastolic BP by 20 seconds. Orthostatic hypotension was defined as a persisting drop in systolic BP ≥20mmHg and/or drop in diastolic BP ≥10mmHg. The association of orthostatic hypotension variants with syncope and unexplained falls events (primary outcome) over 8 years follow up were evaluated using multivariable logistic regression models. Results 4,596 participants were included in this analysis; 953 (20.7%) met criteria for immediate orthostatic hypotension, 1,008 (22.0%) for orthostatic hypotension. Orthostatic hypotension, but not immediate orthostatic hypotension was associated with increased odds of syncope or unexplained falls (Orthostatic hypotension: OR 1.31; 95% CI, 1.04–1.66, Immediate orthostatic hypotension: OR 1.22; 95% CI, 0.93–1.57). Conclusion Immediate orthostatic hypotension is common, and not associated with unexplained falls or syncope. The terminology immediate orthostatic hypotension may be more appropriate.